Inconstitucionalidad de la agravante establecida en el artículo 47 numeral 20 del código orgánico integral penal - Carrión Barco, Milton Iván (Machala : Universidad Técnica de Machala, 2021)
In Ecuador and the Constitution of the Republic, the National Court of Justice is the highest organ of administration of ordinary justice, its president will be the one who represents the Judicial Function of the country; The general function of the National Court of Justice consists of guaranteeing legal security and safe guardianship of the processed person; Based on this context, the objective of the investigation has been proposed to determine the unconstitutionality of the aggravating circumstance established in article 47, numeral 20 of the Comprehensive Organic Criminal Code, for violating the procedural principle of "presumption of innocence", guaranteed in the same body legal, in article 5 numeral 4 and mainly article 76 numeral 2 of the Constitution of the Republic of Ecuador, for this we resorted to bibliographic research of scientific publications published in indexed journals, as well as narrative and jurisprudential reviews; As a result of the investigation, the unconstitutionality of article 47 numeral 20 of the Comprehensive Organic Penal Code could be evidenced, by means of which it is possible that the judge may aggravate the penalty when it comes to a person who has been apprehended in flagrante delicto, for which reason This reality is known as something unlawful, because when an individual is apprehended it does not express that he is guilty, a process must be followed and by means of the enforceable sentence resolve the responsibility of the imputed crime; the process is violated by using prior apprehension as an aggravating factor, violating the right to judicial protection.
En el Ecuador y la Constitución de la República, la Corte Nacional de Justicia es el máximo órgano de administración de justicia ordinaria, será su presidente quien represente a la Función Judicial del país; la función general de la Corte Nacional de Justicia consiste en garantizar la seguridad jurídica y la tutela segura de la persona procesada; con base en este contexto se ha planteado como objetivo de la investigación, determinar la inconstitucionalidad de la agravante establecida en el artículo 47 numeral 20 del Código Orgánico Integral Penal, por vulnerar el principio procesal de “presunción de inocencia”, garantizado en el mismo cuerpo legal, en el artículo 5 numeral 4 y principalmente el artículo 76 numeral 2 de la Constitución de la República del Ecuador, para esto se recurrió a la investigación bibliográfica de publicaciones cientificas publicadas en revistas indexadas, al igual que las revisiones narrativas y jurisprudenciales; como resultado de la investigación se pudo evidenciar la inconstitucionalidad del artículo 47 numeral 20 del Código Orgánico Integral Penal, mediante el cual es posible que el juzgador pueda agravar la pena cuando se trata de una persona que ha sido aprehendida en delito flagrante, por lo que se conoce a esta realidad como algo antijurídico, debido a que cuando un individuo es aprehendido eso no expresa que sea culpable, se debe seguir un proceso y mediante la sentencia ejecutoriada resolver la responsabilidad del delito imputado; se vulnera el proceso al emplear la aprehensión previa como agravante, violando derecho a la tutela judicial.
Keywords: JUSTICIA; SEGURIDAD JURIDICA; DELITO FLAGRANTE; AGRAVANTE